Prediction of distortions and residual stresses in narrow gap weld joints prepared by hot wire GTAW and its validation with experiments. (October 2021) - Das Banik, Sayantan; Kumar, Suranjit; Singh, Pawan Kumar; Bhattacharya, Sujay; Mahapatra, Manas Mohan
Abstract: The present paper aims to predict distortions and residual stresses in thick plate weld joints of austenitic stainless steel material prepared by automatic hot wire gas tungsten arc welding (GTAW) process and narrow gap technique using finite element analysis (FEA). The prediction has been validated by carrying out experiments. The variables considered in welding of plate joints are narrow groove configuration, high deposition rate leading to lower heat input (hot wire GTAW), and stress relieving treatment. A suitable stress-relieving treatment has been proposed for relaxing residual stresses and preventing sensitization of the heat-affected zone (HAZ) of the ASS weld joint. Predicted and experimental results of temperature distribution, distortions, and residual stresses were found to be in good agreement. The applicability of prediction of residual stresses for higher weld thicknesses has also been verified. The nature of residual stresses across thickness has also been compared with that given in Structural Integrity Assessment Procedures for European Industry (SINTAP) and BS 7910 standards. Details of the above finding are discussed in this paper. Highlights: Weld joints produced by hot wire GTAW with narrow gap has resulted in a faster cooling rate with beneficial effects in sensitization, and reduced distortions and residual stresses. A suitable stress relieving heat treatment cycle is proposed to reduce residual stresses and sensitization of HAZ of the ASS weld joint. No significant increase in residual stresses has been observed in the weld region due to clamping. Residual stresses are of the same order for plate weld thicknesses of 20 and 40 mm prepared using the same welding process and clamping conditions.